PENGARUH PEMBELAJARAN BERBASIS MASALAH DAN KEBIASAAN MEMBACA TERHADAP KETERAMPILAN MENULIS KARANGAN EKSPOSISI - Ramayani, Cici (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
The purpose of this research was to explain the influence of problem based learning model and reading habit on the students’ skill to write exposition in class X of SMA Negeri 1 Sungai Limau. This was a quantitative research was 180 which applied 2x2 factorial experimental design. Results of the research, four conclusions were drawn. First, exposition writing skill of the students taught by using problem based learning model was better than that of students taught by using conventional learning. Second, exposition writing skiil of the students having high reading habit taugh by using problem based learning model was better than that of students though by using conventional learning. Third, exposition writing of the students having low reading habit taught by using problem based learning model was better than that of students taught bu using problem based learning. Fourth, there was an interaction between reading habit and problem based learning model in affecting the students’ exposition writing skill in class X of SMA Negeri 1 Sungai Limau